The Effect of Raw Mesocarp Fibre Inclusion on the Durability Properties of Lightweight Foamed Concrete - Md Azree Othuman Mydin (ASEAN Journal on Science and Technology for Development, 2021)
Researchers around the globe have recognised the potential need for lightweight, reliable, easy to use, affordable, and even more sustainable building materials. One of the vanguard proposals has been the procurement, development and use of alternative, non-conventional local building materials, which includes the possibility of utilising lightweight foamed concrete (LFC). LFC is excellent under compression but poor in tensile stress, as it produces multiple microcracks. LFC cannot withstand the tensile stress induced by applied forces without additional reinforcing elements. This research was conducted to examine the potential utilisation of oil palm mesocarp fibre-reinforced (OPMF) LFC in terms of its durability. Two densities, 600 kg/m3 and 1,200 kg/m3, were cast and tested with five different percentages of OPMF, which were 0.00% (control), 0.15%, 0.30%, 0.45% and 0.60%. The parameters evaluated were water absorption, porosity, drying shrinkage, ultrasonic pulse velocity. The results revealed that the inclusion of OPMF in LFC helps to minimise water absorption and the porosity of LFC. Moreover, the inclusion of OPMF also improves the drying shrinkage and ultrasonic pulse velocity of LFC.